Disease Burden and Harm of Osteoarthritis - WU Haotian; LIN Jianhao (Xiehe Yixue Zazhi)
Osteoarthritis, the most common degenerative musculoskeletal disease, has an increasingly heavy burden around the world. In 2019, approximately 530 million people suffered from osteoarthritis, with the age-standardized incidence rate of 492.2 per 100 000, the age-standardized prevalence rate of 6348.3 per 100 000 and the age-standardized rate of disability-adjusted life years (DALYs) of 228.0 per 100 000. The heaviest burden is observed in high-income North America while the fastest growth of burden is observed in high-income Asia Pacific. The age-standardized rate of incidence, prevalence and DALYs in China were 509.8 per 100 000, 6330.1 per 100 000 and 224.8 per 100 000, respectively, which were higher than the average level in Asia. Considering the large and aging population in China, the disease burden will continue to increase and the prevalent number and DALYs in 2044 are expected to be 1.5 times higher than those in 2019. Although osteoarthritis is frequently seen in the elderly, the negative impact on young adults should not be ignored. Besides, postmenopausal women, individuals with high body mass index, and residents in rural and mountainous areas are also at relatively higher risk of osteoarthritis. Osteoarthritis increases the risk of multiple diseases, including cardiovascular diseases, diabetes and psychological cognitive impairment, as well as the sarcopenia and fractures. The increasing disease burdens and medical requirements in China indicate that clinicians have to fully understand the burden and harm of the disease, and conduct initial screening and intervention for the osteoarthritis-related diseases for patients. The long-term goal is to relieve the disease burdens and to improve the quality of life for osteoarthritis patients.